1981
DOI: 10.1111/j.1471-0528.1981.tb01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Osmolality and Urinary Concentration and Dilution During and After Pregnancy: Evidence That Lateral Recumbency Inhibits Maximal Urinary Concentrating Ability

Abstract: Summary In nine women studied serially before conception and through the first trimester, plasma osmolality (Posm) started to decline with the first missed menstrual period, was significantly decreased by the fifth week of pregnancy and was 10 mosmol/kg lower than preconception values by the tenth week, changing little thereafter. Changes in plasma sodium (and its attendant anion) accounted for the majority of the decrement. In separate studies, urinary concentration and dilution, assessed by water deprivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(52 citation statements)
references
References 26 publications
5
47
0
Order By: Relevance
“…Theor etically, reduced circulating AVP levels might be antici pated during salt restriction. As reported by Davison et al (1981), decreased solute diuresis, as in restricted-salt diets, lowers distal tubular flow. Therefore, the fraction of solute escaping reabsorption and the residual volume to be concen trated are decreased, requiring decreased tubular binding of AVP.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Theor etically, reduced circulating AVP levels might be antici pated during salt restriction. As reported by Davison et al (1981), decreased solute diuresis, as in restricted-salt diets, lowers distal tubular flow. Therefore, the fraction of solute escaping reabsorption and the residual volume to be concen trated are decreased, requiring decreased tubular binding of AVP.…”
Section: Discussionsupporting
confidence: 61%
“…Perhaps, in our study, diminished AVP plasma levels might have escaped detection because of assay sensitivity (see Introduction) or because patients in our study were positioned in the left lateral tilt position, neces sary for simultaneous Doppler flow measurements of the fetal and uterine circulation. In this position, the maximal concentrating ability of the kidney is diminished probably because of intravascular mobilized interstitial fluids which will consequently suppress AVP release (Davison et al 1981). Possible differences in neurophysin or AVP levels due to dietary restrictions might therefore have been blunted.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease starts by the first missed menstrual period and gradually decreases until the tenth week of gestation, which does not change later on (71). Serum sodium is decreased by about 4-5 mEq/ml due to this reset osmostat.…”
Section: Posterior Pituitarymentioning
confidence: 91%
“…This decrease in osmolality is accompanied by parallel decreases in the main extracellular fluid electrolytes, mainly sodium and its attendant ion chloride, as well as urea. 3 Furthermore, this group demonstrated robustly that the explanation for the observed decreases was not due simply to haemodilution, a commonly held and accepted explanation for most of the observed physiological changes in normal pregnancy, but was due instead to the lowering of the osmotic thresholds for both vasopressin release and thirst to the observed lower osmolality values. 4 This explanation, they argued, was why normally pregnant women were able to continue to concentrate and dilute their urine normally, about their new lower osmolality levels instead of being in a state of continuous diuresis as one would have expected if it was simply due to haemodilution.…”
mentioning
confidence: 87%
“…2 Davison et al 3 in work spanning well over a decade, has demonstrated unambiguously, changes in osmoregulation function in the three trimesters of normal pregnancy, which we now know are physiological, but would have been interpreted as pathological in the context of nonpregnant reference values.…”
mentioning
confidence: 99%